2022
DOI: 10.3389/fmed.2022.799642
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Potassium, Sodium, Glucose, and Hemoglobin Measured by Blood Gas Analyzer With Dry Chemistry Analyzer and Complete Blood Count Analyzer: A Two-Center Retrospective Analysis

Abstract: BackgroundBlood gas analyzers (BGAs) and dry biochemistry analyzers for potassium and sodium are based on direct electrode methods, and both involve glucose oxidase for glucose detection. However, data are lacking regarding whether the results of the two assay systems can be used interchangeably. In addition, there remains controversy over the consistency between BGA-measured hemoglobin and complete blood count analyzer data. Here, we compared the consistency of sodium, potassium, glucose, and hemoglobin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…This is corroborated by a study by Açıkgöz et al, which found significant disparities in potassium measurements between blood gas and biochemical methods in cases of moderate to severe hyperkalemia, mirroring our findings [28]. The marked average biases in our study, compared to other literature, underscore the complexity of potassium measurement and its implications [17,25]. Furthermore, the study by Johnston et al underscores that measurement discrepancies in hyperkalemia and cardiac arrest scenarios reflect not only the limitations of the devices but also the dynamic nature of patient-specific factors [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is corroborated by a study by Açıkgöz et al, which found significant disparities in potassium measurements between blood gas and biochemical methods in cases of moderate to severe hyperkalemia, mirroring our findings [28]. The marked average biases in our study, compared to other literature, underscore the complexity of potassium measurement and its implications [17,25]. Furthermore, the study by Johnston et al underscores that measurement discrepancies in hyperkalemia and cardiac arrest scenarios reflect not only the limitations of the devices but also the dynamic nature of patient-specific factors [29].…”
Section: Discussionsupporting
confidence: 91%
“…Despite no statistically significant difference in Lin's concordance analysis, the correlation was higher in elderly patients, suggesting no compromised concordance between blood gas and biochemistry methods for sodium measurements in this group. Previous studies by Xie et al and Triplett et al support our findings of strong concordance, despite observed average biases [17,25]. These results underscore the importance of precise evaluation of blood gas results in emergency medicine for both elderly and non-elderly patients, especially when dealing with life-threatening conditions.…”
Section: Discussionsupporting
confidence: 89%